REMOTE SENSING USING UNMANNED AERIAL VEHICLES FOR TOURIST-RECREATION LAKE EVALUATION AND DEVELOPMENT - Borkowski, Grzegorz; Młynarczyk, Adam (Quaestiones Geographicae, 2019)
This article concerns the use of remote sensing methods to assess the potential of tourism and recreation of lakes by using unmanned aerial vehicles as a tool that offers new measurement possibilities in such difficult areas to research as river and lake systems. For the purpose of the study, air surveys over three lakes used for tourism and recreation purposes were planned and carried out. These were the following lakes: Swarzędzkie, Wolsztyńskie and Zbąszyńskie located in western Poland. The photos were taken with a RGB and a multispectral cameras. On the basis of calculated orthophotomaps and digital surface models, anthropogenic and natural values were assessed. The examples of the research show the versatile possibilities of using drones dependent on the type sensor used. Remote sensing performed from the deck of an unmanned aircraft is widely used in the study of lakes and is an alternative to existing land and water research methods.